Subsistema tributário do meio ambiente natural - Barreira, Fábio Nieves (2011)
This dissertation aims to demonstrate that the Republic Constitution protects the value ecologically balanced environment, understood as the balance between being and environment, depending on natural selection, as a condition to healthy living. For the realization of constitutional values, the Highest Law imposes to political entities the duty to grant preferential treatment to products and services, and their development and delivery processes, as the environmental impact they cause to the environment. The tribute is an outstanding instrument to the protection of ecologically balanced environment, providing the environmental and tributaries principles of the Constitution that delimit the scope of environmental taxation, creating an environmental tax constitutional subsystem. Thus, political entities shall provide differential tax treatment through selectivity, progressivity and tax benefits, to products and services and their development and provision processes, according to the intensity of the environmental impact to the environment that they cause, demonstrated by a study of environmental impact, affecting the behavior of the market to develop in a sustainable way and granting to the property its social function. They must also collect taxes whose incidence allows the protection of ecologically balanced environment